Writing and Reading (with) Polar Bears in Yoko Tawada's Etüden im Schnee (2014)*. (10th February 2019) - McNeill, Elizabeth
Abstract : This article draws upon Tawada's reflections on language and metamorphosis to argue that the polar bears in Etüden im Schnee (2014 ) complicate literary animal studies' tendency to locate the continuity between human and animals in their shared bodily vulnerability. Instead of using language as a mere springboard into theorizing embodiment, Tawada highlights humans' and animals' shared capacity to think and speak—abilities that traditionally have been employed to separate humans from animals. Tawada's polar bears not only read and write but play with language and the distinctly "human" spaces and genres in which language has typically been employed. The bears' games with language throw into relief how specifically lingual spaces, particularly literature, can both border off human from animal and collapse that very border. This article proposes that Tawada's polar bears ultimately articulate a rich theory of language that draws on a German tradition of both theories of language and literary animals.